Live Donor Kidney Transplantation: Altruism Alone Is Not Always Enough!. Issue 8 (August 2018) - Molinari, Michele; Hariharan, Sundaram
Abstract : In this short and provocative review, the authors dissect the costs related to each step of the process of kidney living donation whatever the country, the healthcare system and the number of procedures.